2011
DOI: 10.1158/1541-7786.mcr-09-0237
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD44 as a Surface Biomarker for Drug Resistance by Surface Proteome Signature Technology

Abstract: We developed surface proteome signatures (SPS) for identification of new biomarkers playing a role in cancer drug resistance. SPS compares surface antigen expression of different cell lines by immunocytochemistry of a phage display antibody library directed to surface antigens of HT1080 fibrosarcoma cells. We applied SPS to compare the surface proteomes of two epithelial derived cancer cell lines, MCF7 and NCI/ADR-RES, which is drug resistant because of overexpression of the P-glycoprotein (P-gp) drug efflux p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
(48 reference statements)
4
27
0
Order By: Relevance
“…Until now, only few studies have analyzed the surfaceome of chemoresistant cells [8, 9]. These studies have identified proteins that were overexpressed in MDR cells, such as CD44 [8], dihydropyridine receptor alpha 2 and laminin subunit alpha 5 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only few studies have analyzed the surfaceome of chemoresistant cells [8, 9]. These studies have identified proteins that were overexpressed in MDR cells, such as CD44 [8], dihydropyridine receptor alpha 2 and laminin subunit alpha 5 [9].…”
Section: Introductionmentioning
confidence: 99%
“…CD44 expression is also considered as an important biomarker to predict the sensitivity of chemotherapy in ovarian cancer, fibrosarcoma and Gastric cancer [8,46,48]. And CD44 abnormal expression can directly affect the emergence of drug-resistant phenotype [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for nanoparticle-based immunotargeting against tumor antigens which overexpressed on the cancer cell surface, the antibodies were conjugated with nanoparticulate drug delivery systems to provide immunoconjugates that conferred the greater selectivity to the drug and the higher uptake by means of receptormediated endocytosis [38]. CD44 exhibits as a potential biomarker for drug resistance [23]. An immunohistochemical analysis of breast cancer tissue from untreated female patients demonstrated a statistical correlation between CD44 and P-gp expression [45].…”
Section: Examination Of the Effect Of Dmsn-cd44 In Vivomentioning
confidence: 99%
“…CD44 is overexpressed in breast cancer stem cells and MDR breast cancer cells [22][23][24]. There is strong evidence that CD44 is involved in inducing transcriptional up-regulation of the MDR1 gene to promote MDR [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation